IMPLEMENTASI METODE BERMAIN PERAN UNTUK MENINGKATKAN KECERDASAN INTERPERSONAL ANAK USIA 5-6 TAHUN DI TK BARUNAWATI - Sumanti M. Saleh; Sugito Sugito (Universitas Negeri Yogyakarta, 2015)
The study aims to increase interpersonal intelligence of children aged 5-6 years in kindergarten Barunawati Ternate City and how much the increase in interpersonal intelligence of children aged 5-6 years using role playing methods. This research is a classroom action research conducted in two cycles. The subjects in this study are students in kindergarten group B Barunawati Ternate City amounting to 25 people. The collaborators in this research were the B-grade teachers acting as the executor, while the researcher was an observer and as a teacher assistant in the observation. The data were collected through observation, notes field and documentation. Observations included the process of learning social emotional and childrens interpersonal intelligence. Field notes were used to see the problems faced during the learning. Documentation used to obtain data in the form of photos. The data analysis techniques used simple descriptive statistics. The data were analyzed quantitatively and qualitatively. The results of this study shows that early childhood interpersonal intelligence can be improved through the role playing methods. The increase in the amout of 76%.